Differential proteomics analysis of mononuclear cells in cerebrospinal fluid of Parkinson’s disease - Xing, Lifei (Int J Clin Exp Pathol, 2015)
Parkinson’s disease (PD) is one common neurodegenerative disease featured with degeneration of dopaminergic neurons in substantia nigra. Multiple factors participate in the pathogenesis and progression of PD. In this study, we investigated the proteomics profiles of mononuclear cells in cerebrospinal fluids from both PD patients and normal people, in order to explore the correlation between disease factors and PD. Cerebrospinal fluid samples were collected from both PD and normal people and were separated for mononuclear cells in vitro. Proteins were then extracted and separated by 2-dimensional gel electrophoresis. Proteins with differential expressions were identified by comparison to standard proteome expression profile map, followed by software and database analysis. In PD patients, there were 8 proteins with consistent expression profile and 16 proteins with differential expressions. Those differential proteins identified include cytoskeleton proteins (actin, myosin), signal transduction proteins (adenosine cyclase binding protein 1, calcium binding protein, talin) and anti-oxidation factor (thioredoxin peroxide reductase). PD patients had differential protein expressional profiles in the mononuclear cells of cerebrospinal fluids compared to normal people, suggesting the potential involvement of cytoskeleton and signal transduction proteins in apoptosis of neuronal apoptosis and PD pathogenesis.